EVALUASI PELAKSANAAN PROGRAM PENGEMBANGAN PERUMAHAN (STUDI PADA KANTOR DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KOTA PALEMBANG) - Yuliana Yuliana (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
Housing and settlements are basic human needs. Therefore, the government is trying to meet the community's need for housing. This study aims to see how the housing development program is implemented in Palembang City, monitor this program and also monitor the extent of the housing development program. This research uses descriptive qualitative techniques with interviews. Key information is the Head of the Palembang City Housing and Settlement Area Office, the Head of the Housing and Settlements Section, the Head of the Palembang City Development Planning Agency, and Housing Developers in Palembang City, as well as people living in housing in Palembang City. Then the data obtained from the study were analyzed using qualitative descriptive analysis methods. The results showed that the implementation of the housing development program in Palembang City has not been carried out properly in accordance with what has been planned by the Palembang City Government.